Castle Place, Belfast. (27185911533) - Robert French (Wikimedia Commons, 1880)
Carte postale ancienne issue de Wikimedia Commons. Titre: Castle Place, Belfast. (27185911533). We stay north of the border again today, with this lovely shot of Castle Place in the center of Belfast. Gaslight, horse drawn trams and lots of action, what more could you ask for. We seem to see people alighting and getting ready to board the tram in the foreground - obviously doing so in the middle of the road (with traffic on both sides). I wonder what constitutes a "stop" on the system? As was pointed-out today, we've visited this area of Belfast a few times before, though perhaps with not quite as much activity. With thanks in particular to [/photos/gnmcauley/ Niall McAuley] and his research of the Public Record Office of Northern Ireland (PRONI) business and street directories, we can likely refine the 50 year catalogue range to a decade or so ca.1880-1890. This is corroborated by [/photos/beachcomberaustralia/ beachcomberaustralia]' s expertise in late 19th century ladies fashions:) Photographer: Robert French Collection: Lawrence Photograph Collection Date: Catalogue range ca.1865-1914. But likely ca.1880-1890 NLI Ref: L_CAB_04198 You can also view this image, and many thousands of others, on the NLIs catalogue at catalogue.nli.ie
Licence No known copyright restrictions via Wikimedia Commons
Keywords: carte postale; image; patrimoine; histoire locale; wikimedia commons; gare; Château